2015
DOI: 10.1021/cg501861t
|View full text |Cite
|
Sign up to set email alerts
|

Spherical and Porous Particles of Calcium Carbonate Synthesized with Food Friendly Polymer Additives

Abstract: Porous calcium carbonate particles were synthesized by adding solutions of Ca 2+ to solutions of CO 3 2− containing polymeric additives. Under optimized conditions welldefined aggregates of the anhydrous polymorph vaterite formed. A typical sample of these micrometer-sized aggregates had a pore volume of 0.1 cm 3 /g, a pore width of ∼10 nm, and a specific surface area of ∼25−30 m 2 / g. Only one mixing order (calcium to carbonate) allowed the formation of vaterite, which was ascribed to the buffering capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…They are administered by various routes, including transdermal 19,22 , inhalation 20 , intertumoral 21 , and peroral 23 . Vaterite particles are also used in the preparation of food-friendly polymer additives 24 and in water purification 25 . However, their transfer from R&D to industrial application has been made difficult by the lack of an efficient loading approach.…”
Section: Introductionmentioning
confidence: 99%
“…They are administered by various routes, including transdermal 19,22 , inhalation 20 , intertumoral 21 , and peroral 23 . Vaterite particles are also used in the preparation of food-friendly polymer additives 24 and in water purification 25 . However, their transfer from R&D to industrial application has been made difficult by the lack of an efficient loading approach.…”
Section: Introductionmentioning
confidence: 99%
“…Control over the crystal growth provides one with a simple way to adjust the crystal porosity even without any additives. 25,26 The surface of the nanocrystallites can be coated with different materials, for example, lipids, for protection. 27 Some recent efforts have been made in the size reduction of calcium carbonate crystals that open new perspectives to employ the crystals for a wide range of administration routes in modern drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In order to control the morphology of CaCO 3 , crystallization methods involving anionic small molecules 8,9 or anionic polymers [10][11][12] were studied by mimicking the formation process of biominerals. We have also reported that monodispersed mesoporous CaCO 3 microspheres with 20 nm mesopores and controllable particle size can be obtained by a biomimetic process.…”
Section: Introductionmentioning
confidence: 99%